A new Era of Personalized Medicine for Cystic Fibrosis – at Last! - Bradley S Quon; Pearce G Wilcox (Canadian Respiratory Journal)
The gene responsible for cystic fibrosis (CF) was discovered 25 years ago. This breakthrough has enabled a sophisticated understanding of how various mutations lead to specific alterations in the structure and function of the CF transmembrane regulator (CFTR) protein. Until recently, all therapies in CF were focused on ameliorating the downstream consequences of CFTR dysfunction. High-throughput drug screening approaches have yielded compounds that can modify CFTR structure and function, thus targeting the basic defect in CF. The present article describes the CFTR mutational classes, reviews mutation-specific therapies currently in late-phase clinical development, and highlights research opportunities and challenges with personalized medicine in CF.